Four new species of Estheria Robineau-Desvoidy (Diptera: Tachinidae) from China and Nepal, with a review of the East Palearctic and Oriental species - Zhang, Chun-Tian; Shima, Hiroshi; Liang, Hou-Can; Li, He-Nan (Zootaxa, 2019)
The species of Estheria Robineau-Desvoidy (Diptera: Tachinidae) from the East Palearctic and Oriental regions are reviewed. Eighteen species are recognized: the fourteen previously described, E. acuta (Portschinsky, 1881), E. alticola Mesnil, 1967, E. bucharensis (Kolomiets, 1974), E. cinerella Mesnil, 1967, E. cristata (Meigen, 1826), E. decolor (Pandellé, 1896), E. flavipennis Herting, 1968, E. lacteipennis Mesnil, 1967, E. maculipennis Herting, 1968, E. magna (Baranov, 1935), E. nigripes (Villeneuve, 1920), E. pallicornis (Loew, 1873), E. petiolata (Bonsdorff, 1866) and E. picta (Meigen, 1826), and four species described as new to science, E. hirtinerva Zhang & Shima sp. nov. (W China, Nepal), E. prostata Zhang & Shima sp. nov. (W China, Nepal), E. tibetensis Zhang & Shima sp. nov. (W China, Nepal) and E. wangi Zhang & Liang sp. nov. (W China, Pakistan). Estheria acuta and E. decolor are newly recorded for China, E. magna is newly recorded for Malaysia, Pakistan and Vietnam, and E. pallicornis is newly recorded for Nepal. An identification key to the 18 species of Estheria so far known from the East Palearctic and Oriental regions is included, together with 126 figures of heads and habitus of males and females, and male terminalia and known distributions.